Avaliação de sintomas de ansiedade e de depressão em pacientes hospitalizados no pós-intervenção coronária percutânea - Della Méa, Cristina Pilla (2017)
Cardiovascular diseases are among the leading causes of disability and death. One of the forms of treatment for them is the percutaneous coronary intervention (PCI). The objective of this study is to evaluate the anxiety and depressive symptoms in adult and elderly patients hospitalized after PCI. In addition, it was identified the sociodemographic profile of adult and elderly patients hospitalized after PCI; assess the risk factors for cardiovascular disease with anxiety and depressive symptoms in adult and elderly patients hospitalized after PCI. It is a cross-sectional study conducted with 266 patients, men and women, who underwent PCI in a referral hospital in southern Brazil. The data collection occurred on an individual basis in the period in which the patient was hospitalized. As instruments, were used a questionnaire; the Beck Depression Inventory - Second Edition (BDI-II) and the Beck Anxiety Inventory (BAI). For data analysis, were applied the chi-square test, ANOVA and linear correlation was used to analyze the data collected. The level of significance was p ≤ 0.05. As for the demographic profile, the results showed that the mean age was 64.5 years (SD = 8.9 years), and the majority of male patients (68%), married (72.9%), who live with someone (80.1%), have children (94.4%) and have basic education (80.1%). The diagnosis of most patients was acute myocardial infarction (64.3%), being performed angioplasty with stent placement (95.1%), by the Public Health System (97,7%). In relation to anxiety symptoms, the majority presented them in serious level (29.7%) and depressive symptoms of minimal intensity (51.9%). Regarding risk factors, the majority had a diagnosis of heart disease in the family (62.8%), was hypertension (83.5%) and presented dyslipidemia (51.5%), however, did not have diabetes (61.7%) or were obese (81.6%). With regard to anxiety symptoms, there was a significant difference in age (p = 0.026), family history of cardiac diagnosis (p = 0.011) and previous diagnosis of depressive disorder (p = 0.011). Women showed symptoms of anxiety to severe level (p < 0.001) and depression of severe intensity more prevalent (p < 0.001). Patients who have already had a diagnosis of depression prior to the ICP, had higher scores of depressive symptoms in the severe intensity (p = 0.001). It is concluded that the anxiety and depressive symptoms in post-ICP should be evaluated and treated, because interfere negatively in the life of the cardiac patients, allowing lower adherence to medical treatment, difficulty in changing the style of life and, consequently, a poorer quality of life. It´s emphasized the importance of a professional of psychology to accompany these patients during hospitalization by ICP.